Engrafted nitrergic neurons derived from hPSCs improve gut dysmotility in mice - Homa Majd; Ryan M. Samuel; Andrius Cesiulis; Jonathan T. Ramirez; Ali Kalantari; Kevin Barber; Sina Farahvashi; Zaniar Ghazizadeh; Alireza Majd; Angeline K. Chemel; Mikayla N. Richter; Subhamoy Das; et al. (Nature, 2025)
Abstract Gastrointestinal (GI) motility disorders represent a major medical challenge, with few effective therapies available. These disorders often result from dysfunction of inhibitory nitric oxide (NO)-producing motor neurons in the enteric nervous system, which are essential for regulating gut motility. Loss or dysfunction of NO neurons is linked to severe conditions, including achalasia, gastroparesis, intestinal pseudo-obstruction and chronic constipation1,2. Here we introduce a platform based on human pluripotent stem cells (hPSCs) for therapeutic development targeting GI motility disorders. Using an unbiased screen, we identified drug candidates that modulate NO neuron activity and enhance motility in mouse colonic tissue ex vivo. We established a high-throughput strategy to define developmental programs driving the specification of NO neurons and found that inhibition of platelet-derived growth factor receptors (PDGFRs) promotes their differentiation from precursors of the enteric nervous system. Transplantation of these neurons into NO-neuron-deficient mice led to robust engraftment and improved GI motility, offering a promising cell-based therapy for neurodegenerative GI disorders. These studies provide a new framework for understanding and treating enteric neuropathies.